Numerical modeling of fracture processes of bodies with stress concentrators under conditions of proportional loading, taking into consideration the statistical distribution of ultimate strength and partial loss of load bearing capacity - Eugeniia Feklistova; Artur Mugatarov; Valeriy Wildemann (Fracture and Structural Integrity, 2025)
This work is dedicated to the development of a fracture model for an elastic-brittle solid with statistically distributed strength characteristics of subregions and the application of this model to describe fracture processes of bodies with stress concentrators under biaxial loading. The methodology of numerical modeling of deformation and fracture processes is improved to take into account the partial loss of load bearing capacity and the appearance of local anisotropy. Based on the improved methodology, modified algorithm is developed. The influence of the biaxial loading mode and the dispersion of the ultimate strength distribution on the loading diagrams and the orientation of the macrodefect is considered. The realization of the gradual macrodefect development (localized type of damage accumulation) or its growth through the most weakened damaged areas (mixed type) is revealed. The applicability of the approach to assessing the type of damage accumulation based on the analysis of numerical solutions of boundary value problems within the elasticity theory is demonstrated. The efficiency of the usage of the modified approach to ensure the reliability and safety of critical structures under multiaxial loading is concluded.